2002
DOI: 10.1021/om0101745
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Chain Formation on Metallic Arrays. X-ray Structural Determinations of [Ru44-(CCC(CO2Me)C(CO2Me))(η-C5H4R)2(μ-CO)(CO)8], [{Ru(CO)2(η-C5H5)}2{μ-CCC(CO2Me)C(CO2Me)C(O)}], and [{Ru(CO)2(η-C5H5)2{μ-CC(CN)2CC(CN)2}] (R = H, Me)

Abstract: The open, planar Ru 4 C 2 compounds [Ru 4 (µ 4 -CC)(η-C 5 H 4 R) 2 (µ-CO) 2 (CO) 8 ] (R ) H, Me) react with the activated electron-deficient alkyne dimethyl acetylenedicarboxylate, (CO 2 Me) 2 C 2 (DMAD), to afford a number of products. One of these was found to contain a metallacyclopentadiene ligand ligated at the 1-and 2-positions by Ru(η-C 5 H 4 R) groups, and another was a new Ru 2 compound resulting from the coupling of DMAD, C 2 , and CO to produce a five-carbon chain.a C(100) is the centroid of the Cp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 48 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…We have found that the CpRu(CO) 2 moiety is extremely flexible in its mode of coordination and has allowed us to investigate a number of unusual bonding situations. Thus, we first decided to attempt the formation of mono-alkynyl complexes to provide suitable models for the formation of oligomeric complexes.…”
Section: Resultsmentioning
confidence: 99%
“…We have found that the CpRu(CO) 2 moiety is extremely flexible in its mode of coordination and has allowed us to investigate a number of unusual bonding situations. Thus, we first decided to attempt the formation of mono-alkynyl complexes to provide suitable models for the formation of oligomeric complexes.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] We have for some considerable time explored the chemistry associated with the CpRu(CO) 2 moiety because of the conformational flexibility it exhibits, which has allowed the isolation of many interesting complexes. [13][14][15][16][17][18][19][20][21][22] In the course of preparing [CpRu(CO) 2 Br] using a minor modification of the published procedure 23 (using bromoform rather than CBr 4 ) we discovered that the reaction did not proceed according to our expectations, Scheme 1, giving not only the expected bromide complex but also gave appreciable contamination with hexabromoethane.…”
Section: Introductionmentioning
confidence: 99%
“…Electron counting indicates that the Ru11−Ru12 interaction is a dative bond from Ru12 to Ru11 (2.795(1) Å). Koutsantonis et al reported formation of a related compound, 12 , from (μ 4 -CC)Ru 4 Cp 2 (CO) 10 ( 11 ) (the RuCp analogue of 2 ) and dimethyl acetylenedicarboxylate (Scheme ) . In comparison to the case for 11 , complex 12 contains one more CO ligand, which causes cleavage of one of the two CpRu−Ru bonds.…”
Section: Resultsmentioning
confidence: 99%